ENHANCING THE COMPETITIVENESS OF HIGHER EDUCATION GRADUATES THROUGH THE INTEGRATION OF SOFT SKILLS INTO EDUCATIONAL PROGRAMS - Uzakova, Vazira Saidmuradovna (THE INNOVATION ECONOMY, 2026)
This article examines the issues of enhancing the competitiveness of higher education graduates in the context of modern labor market requirements. The analysis of the literature review of international studies shows that one of the most effective approaches to developing students’ soft skills is their integration into the educational programs. A survey was conducted on the topic of “Criteria for Selecting University Graduates by Employers” to identify the requirements that modern employers require from graduates.